Quasi-one dimensional in-plane conductivity in filamentary films of PEDOT:PSS - Ruit, Kevin van de; Cohen, Racheli Itzhak; Bollen, Dirk; Mol, Antonius Maria Bernardus van; Yerushalmi‐Rozen, Rachel; Janssen, René A. J.; Kemerink, Martijn (Advanced functional materials, 2013)
The mechanism and magnitude of the in-plane conductivity of poly(3,4-ethy-lenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) thin films is determined using temperature dependent conductivity measurements for various PEDOT:PSS weight ratios with and without a high boiling solvent (HBS). Without the HBS the in-plane conductivity of PEDOT:PSS is lower and for all studied weight ratios well described by the relation $ \sigma = \sigma _0 \rm exp[- \left(T_0øverT \right)^0.5] $ with T0 a characteristic temperature. The exponent 0.5 indicates quasi-one dimensional (quasi-1D) variable range hopping (VRH). The conductivity prefactor σ0 varies over three orders of magnitudes and follows a power law σ0∝c3.5PEDOT with cPEDOT the weight fraction of PEDOT in PEDOT:PSS. The field dependent conductivity is consistent with quasi-1D VRH. Combined, these observations suggest that conductance takes place via a percolating network of quasi-1D filaments. Using transmission electron microscopy (TEM) filamentary structures are observed in vitrified dispersions and dried films. For PEDOT:PSS films with HBS, the conductivity also exhibits quasi-1D VRH behavior when the temperature is less than 200 K. The low characteristic temperature T0 indicates that HBS-treated films are close to the critical regime between a metal and an insulator. In this case, the conductivity prefactor scales linearly with cPEDOT, indicating the conduction is no longer limited by a percolation of filaments. The lack of observable changes in TEM upon processing with the HBS suggests that the changes in conductivity are due to a smaller spread in the conductivities of individual filaments, or a higher probability for neighboring filaments to be connected rather than being caused by major morphological modification of the material.